1999
DOI: 10.1016/s1201-9712(99)90032-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomass cooking fuels and prevalence of tuberculosis in India

Abstract: Results strongly suggest that use of biomass fuels for cooking substantially increases the risk of tuberculosis in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 29 publications
3
118
2
6
Order By: Relevance
“…A few studies have found an increased risk of tuberculosis from exposure biomass fuels, although none of them measured the level of exposure specifically and confounding not fully accounted for in one (26)(27)(28). In these studies, adjusted OR for socio-economic factors OR were 2.58 (1.98-3.37), 2.4 (1.04-5.6) (26-28).…”
Section: Iap Has Been Considered a Risk Factor For Copd By The Globalmentioning
confidence: 99%
“…A few studies have found an increased risk of tuberculosis from exposure biomass fuels, although none of them measured the level of exposure specifically and confounding not fully accounted for in one (26)(27)(28). In these studies, adjusted OR for socio-economic factors OR were 2.58 (1.98-3.37), 2.4 (1.04-5.6) (26-28).…”
Section: Iap Has Been Considered a Risk Factor For Copd By The Globalmentioning
confidence: 99%
“…According to the International Development Association figures, each patient infect on an average about another 10 people and accounts for about 100 million workdays lost due to the illness every year with an equivalent indirect costs of about US$3 billion. Millions of Indian inhabitants have this disease in active form with about half a million dying every year [42]. National Family Health Survey of India showed that people living in households that use wood and dung for cooking are 2.6 times more likely to suffer from active tuberculosis compared with adults residing in households using cleaner fuels.…”
Section: The Iaq Related Health Problems In Rural and Urban Settings mentioning
confidence: 99%
“…After multivariate analyses, stillbirth has been associated with biomass fuel use by pregnant women in one Indian study (ORϭ1.5) [28] and with low birth-weight in Guatemala [29]. After multivariate analyses, tuberculosis and blindness (cataracts) have been shown to be related to use of biomass fuels in two national and two local studies in India [30], [31], [32], [33]. Unfortunately all these studies relied on the type of stove or fuel as the indicator of pollution.…”
Section: Health Effects Of Indoor Air Pollutionmentioning
confidence: 99%